Czy „gatunek” to „rodzaj”? W gąszczu genologii polonistycznej i germanistycznej - Hanus, Anna (Stylistyka, 2020)
The aim o f this article is to outline the terminological differences and dissimilarities in studies on texts, as well as present problems in classification of texts or, morę specifically, difficulties in their descriptions in German and PolLh philological reflection and in fmding common points in defining particular phenomena and terms. This is an attempt at systematization in order to avoid terminological discrepancies and the misunderstanding of terms. The article also shows various research methods within the linguistic genealogy in the contrastive approach, and their significant influence on shaping and grounding particular terms. It seems crucial in this context to outline the newest trends within the scope of scientific interest of German linguistic genealogy, taking into account morę and morę clearly articulated postulates emphasizing the necessity o f extending the rangę of studies in this field to include literary texts, which in cońseąuence may lead to necessary terminological verification.